Sex worker unionization : global developments, challenges and possibilities - Gall, Gregor (Basingstoke, 2016)
"Sex Worker Unionisation examines the challenges and opportunities offered by unionisation for Sex Workers. Exploring unionisation projects undertaken by Sex Workers in most major economies, this ground-breaking study shows how sex-workers have collectively sought to control and organise their work and working lives by co-determining the wage-effort with their de facto employers. It highlights the range of significant obstacles that have impeded their progress, including owner hostility, state regulation and the sway of radical feminism that is present in many unions. Outlining a more efficacious model for sex worker unionisation based upon combining occupation unionism and social movement unionism, this pioneering and controversial new book offers an important study of business organization in a unique industry."